Triterpenoid saponin augmention of saporin-based immunotoxin cytotoxicity for human leukaemia and lymphoma cells is partially immunospecific and target molecule dependent. (February 2015) - Holmes, Suzanne E.; Bachran, Christopher; Fuchs, Hendrik; Weng, Alexander; Melzig, Matthias F.; Flavell, Sopsamorn U.; Flavell, David J.
Abstract Context: Saponinum album (SA) is a complex mixture of triterpenoid saponins previously shown to augment the cytotoxicity of the type I ribosome-inactivating protein saporin and an EGF-saporin target toxin that could potentially be used to improve the therapeutic window of targeted toxins. Objective: To investigate the augmentative property of SA on saporin and saporin-based immunotoxins (IT) directed against five different cell surface target molecules on human leukemia and lymphoma cells. Materials and methods: After determining the optimum dose of SA for each cell line, the extent of SA-mediated augmentation was established for saporin and five saporin-based ITs using XTT and an annexin V apoptosis assay. Immunospecificity was investigated using three different blocking assays. Dose-scheduling was also investigated using the XTT assay. Results: Uncorrected SA-mediated augmentation ranged at best from 31.5 million-fold to, at worse, 174-fold. However, when the calculated fold-increases were adjusted for the non-immunospecific effects of SA on an off-target IT, the true augmentative effects of SA were found to be largely non-immunospecific. Antibody blocking studies demonstrated that the augmentative effect of SA was only partially immunospecific. Separate exposure of target cells to IT and SA at different times demonstrated that immunospecific augmentation of IT by SA could be achieved but only if cells were exposed to IT first and SA second. Conclusions: SA significantly, although variably, augments the cytotoxicity of saporin and saporin-based immunotoxins. Concomitant exposure to both IT and SA can result in non-immunospecific cytotoxicity that can be overcome by temporally separating exposure to each.